USE OF EMPATHY STRATEGIES IN THE SPEECH OF DOCTORS - Kurbanova Nargiza Abdisoatovna (Sciental Journals Publishing, 2025)
In modern medical communication, the use of empathy-based linguistic strategies has become one of the most influential elements of doctor–patient interaction. The rhetorical skills of medical professionals, the ability to choose appropriate lexical, syntactic, and paralinguistic units, and the culturally-specific norms of English and Uzbek communication styles significantly determine the psychological and emotional state of the patient. Recent linguistic studies in many countries focus on the features of medical discourse, the role of empathy in dialogic speech, as well as the phonetic, lexical, and rhetorical indicators that strengthen trust between the doctor and the patient. This article analyzes empathy strategies in English and Uzbek medical discourse, examines similarities and differences between rhetorical devices, and provides examples derived from real medical communication.
Keywords: Empathy, medical discourse, rhetorical strategies, reassurance, patient anxiety, euphemism, paralinguistic signals.